Learning outcome of mathematics and science: Features of Indonesian madrasah students - Kusaeri Kusaeri; Ali Ridho (Universitas Negeri Yogyakarta, 2019)
This study aims to analyze the learning outcome of mathematics and sciences in the Indonesian National Examination from 2015 to 2018 of MTs (Islamic secondary school). The results of the analysis are used as the basis for making alternative policy as a possible way to improve the quality of mathematics and science learning. With the sample size of 360, 371 MTs students in East Java, the achievement was measured by using 40 multiple choice questions with each having four answer options. Split-plot and latent profile analysis of the data show that there was a consistent decrease in the achievement of mathematics and sciences of the moderate group of MTs from 2015 to 2018 with a dramatic drop in mathematics and tendency to drop for science. The fundamental implication of these findings is that there is a need for learning innovations to improve mathematics and science learning outcomes for 21st century learning. The findings can also provide data support for decision making for the revision of the mathematics and science curriculum and can be further used as empirical evidence for the developed countries in finding ways to improve the quality of mathematics and science learning outcomes for 21st century learning, in particular, to assist the developing countries such as Indonesia.